APPLICATION OF ERGONOMICS APPROACH TO QUESTIONS OF PREVENTION OF PRODUCTION TRAUMATISM AND PROFESSIONAL DISEASES IN NAFTOGAZOVIY INDUSTRY - Цюпа, Р. В.; Хантя, Н. М.; Кривенко, Г. М.; Семчук, Я. М.; Лялюк-Вітер, Г. Д. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
The analysis of occupational injuries and illnesses in the petroleum industry is examined. The possibility of application of the «people-machine» system for prevention of occupational injuries and professional diseases in oil and gas area is examined. The program for calculation the optimal parameters of the work place and the information fields is elaborated. The diagram of dependence quantity channels connection and information field is given.